Anxiety, depression and post-traumatic stress disorder in refugees resettling in high-income countries: systematic review and meta-analysis. Issue 4 (July 2020) - Henkelmann, Jens-R.; de Best, Sanne; Deckers, Carla; Jensen, Katarina; Shahab, Mona; Elzinga, Bernet; Molendijk, Marc
Abstract : Background: The number of refugees is at its highest since the Second World War and on the rise. Many refugees suffer from anxiety, depression and post-traumatic stress disorder (PTSD), but exact and up-to-date prevalence estimates are not available. Aims: To report the pooled prevalence of anxiety and mood disorders and PTSD in general refugee populations residing in high-income countries and to detect sources of heterogeneity therein. Method: Systematic review with meta-analyses and meta-regression. Results: Systematic searches (final search date 3 August 2019) yielded 66 eligible publications that reported 150 prevalence estimates (total sample N = 14 882). Prevalence rates were 13 and 42% (95% CI 8–52%) for diagnosed and self-reported anxiety, 30 and 40% (95% CI 23–48%) for diagnosed and self-reported depression, and 29 and 37% (95% CI 22–45%) for diagnosed and self-reported PTSD. These estimates are substantially higher relative to those reported in non-refugee populations over the globe and to populations living in conflict or war settings, both for child/adolescent and adult refugees. Estimates were similar over different home and resettlement areas and independent of length of residence. Conclusions: Our data indicate a challenging and persisting disease burden in refugees due to anxiety, mood disorders and PTSD. Knowing this is relevant for the development of public health policies of host countries. Scalable interventions, tailored for refugees, should become more readily available.